Suntec Singapore: Introducing innovations in the MICE industry - LIM, Yun Fong (Institutional Knowledge at Singapore Management University, 2018)
In November 2016, Arun Madhok, CEO of Suntec Singapore (Suntec), a premier convention and exhibition centre in Singapore, was looking at processes in which productivity could be improved. The global MICE industry was becoming increasingly competitive. Suntec’s strategy was to capitalise on its good location while providing a premium venue and good service. Singapore’s pro-business and safe environment were factors for MICE organisers and Madhok partnered with the Singapore Tourism Board (STB) and other local industry participants to attract them to the island. Suntec had recently undergone a major renovation to integrate new technology into its building design. Madhok made use of the downtime to improve his food quality and presentation by sending his staff for training at top hotels. Operationally, many companies were affected by government regulations that introduced quotas for foreign workers. Madhok began a productivity push to review the company’s processes, beginning with dishwashing. A designated dishwashing area would be leased out to a vendor, who could solicit business from F&B outlets throughout the Suntec Mall. It proved to be a success as Suntec’s dishwashing costs decreased and new checks were introduced to ensure the cleanliness of the items. Madhok was now keen to seek other process innovations. Through this case, the participants will better understand how innovative operational processes can be integrated with a company’s strategy. At the end of the case-based lesson, the students should be able to demonstrate how a culture of innovation can be effectively fostered, and explain the different types of innovation that can help any business.